2022
DOI: 10.3390/cancers14123025
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction of Patients with Diffuse Low-Grade Glioma: A Qualitative Review of a Neglected Concern

Abstract: Diffuse low-grade gliomas (LGG) commonly affect young adults and display a slow evolution, with a life expectancy that can surpass 15 years, thanks to multimodal therapeutic management. Therefore, preservation of quality of life (QoL), including sexual health, is mandatory. We systematically searched available medical databases of Pubmed, Cochrane, and Scopus for studies that reported data on sexual activity or dysfunction (SD) in LGG patients. We analyzed results to determine incidence of SD and its associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…SH is a neglected concern in young patients with brain tumors in general, and with LGG in particular. According to a recent systematic review of the limited literature available on SH in neurooncological patients-three studies were found that covered 124 brain tumor patients, of which 62 (50%) had LGG-the incidence of sexual dysfunction ranged from 44 to 63% [19]. The potentially high prevalence of sexual dysfunction among LGG patients, coupled with their young age and extended life expectancy, emphasizes the need for more robust investigations of SH and tailored therapeutic strategies to improve long-term QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SH is a neglected concern in young patients with brain tumors in general, and with LGG in particular. According to a recent systematic review of the limited literature available on SH in neurooncological patients-three studies were found that covered 124 brain tumor patients, of which 62 (50%) had LGG-the incidence of sexual dysfunction ranged from 44 to 63% [19]. The potentially high prevalence of sexual dysfunction among LGG patients, coupled with their young age and extended life expectancy, emphasizes the need for more robust investigations of SH and tailored therapeutic strategies to improve long-term QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently used instruments to measure the patient-reported outcomes of health-related quality of life (QoL) in brain tumor patients include the patient questionnaires European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ) Core 30 (C30) and Brain 20 (BN20) [18]. Sexual dysfunction as a domain of QoL has been recognized as a neglected concern in young brain tumor patients such as those with LGG [19]. The EORTC has recently validated the EORTC QLQ-SH22 questionnaire to assess the sexual health of patients with cancer at different treatment stages and during survivorship for clinical trials and for clinical practice [20].…”
Section: Introductionmentioning
confidence: 99%
“…As well as cognition, emotional status can also be altered by LGG, e.g., deficit of empathy due the invasion of the right arcuate fasciculus or cingulum [ 115 , 116 ], or heightened schizotypal traits related to damage of the left uncinate fasciculus [ 117 ]. This can result in changes of mood or even personality in LGG patients [ 118 ], which may explain possible changes in their social interactions [ 119 ] or sexual activity [ 120 , 121 ]. Therefore, in practice, movement and conation (i.e., the willingness which leads to action) [ 122 ], visuo-spatial cognition, language, executive functions, attention, memory, semantic processing [ 123 , 124 ], mentalizing, metacognition (knowing of knowing) [ 125 ], emotion, personality, and behavior [ 118 ] must be systematically and carefully evaluated in clinical routine at diagnosis, as well as before and after each treatment in LGG patients [ 4 ].…”
Section: Predicting Neural Interindividual Variability and Its Change...mentioning
confidence: 99%
“…In contrast, grade II LGG tumors do involve the aforementioned histologic features [ 19 ]. Symptoms of LGG include headaches, vomiting, blurry vision, memory loss, nausea, and weakness on one side of the body [ 20 , 21 , 22 , 23 ]. LGG causes seizures more frequently than other brain cancers because it is produced in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%